Economic evaluation of the new oral anticoagulants for the prevention of thromboembolic events: a cost-minimization analysis - Marcolino, Milena Soriano; Polanczyk, Carisi Anne; Bovendorp, Ana Carolina Caixeta; Marques, Naiara Silveira; Silva, Lilian Azevedo da; Turquia, Cintia Proveti Barbosa; Ribeiro, Antonio Luiz (São Paulo Medical Journal, 2016)
CONTEXT AND OBJECTIVE: Randomized clinical trials have shown that the new oral anticoagulants have at least similar impact regarding reduction of thromboembolic events, compared with warfarin, with similar or improved safety profiles. There is little data on real costs within clinical practice. Our aim here was to perform economic analysis on these strategies from the perspective of Brazilian society and the public healthcare system. DESIGN AND SETTING: Cost-minimization analysis; anticoagulation clinic of Hospital Municipal Odilon Behrens, Belo Horizonte, MG, Brazil. METHODS: Patients at the anticoagulation clinic were recruited between August and October 2011, with minimum follow-up of four weeks. Operational and non-operational costs were calculated and corrected to 2015. RESULTS: This study included 633 patients (59% women) of median age 62 years (interquartile range 49-73). The mean length of follow-up was 64 ± 28 days. The average cost per patient per month was $ 54.26 (US dollars). Direct costs accounted for 32.5% of the total cost. Of these, 69.5% were related to healthcare professionals. With regards to indirect costs, 52.4% were related to absence from work and 47.6% to transportation. Apixaban, dabigatran and rivaroxaban were being sold to Brazilian public institutions, on average, for $ 49.87, $ 51.40 and $ 52.16 per patient per month, respectively, which was lower than the costs relating to warfarin treatment. CONCLUSION: In the Brazilian context, from the perspective of society and the public healthcare system, the cumulative costs per patient using warfarin with follow-up in anticoagulation clinics is currently higher than the strategy of prescribing the new oral anticoagulants.